Prevalence and association of HIV and tuberculosis status in older adults in South Africa: an urgent need to escalate the scientific and political attention to aging and health - Akokuwebe, Monica Ewomazino; Osuafor, Godswill Nwabuisi; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2024)
Objectives: This study examined the prevalence and sociodemographic factors among older adults with HIV and TB status in South Africa. Methods: This data was cross-sectional and obtained from the 2019 General Household Surveys in South Africa. Adults 50 years and over with reported HIV and TB status were included (N = 9,180,047). We reported statistical analyses of the descriptive, Chi-square and Fisher's exact tests, and binary logistic regression. Results: The study has found a prevalence rate of HIV to be 5.3% and TB to be 2.9% among older adults aged 50 years and above in South Africa. However, the study found HIV and TB to be highest among older adults residing in Gauteng, KwaZulu-Natal and Eastern Cape provinces. For HIV status, the female gender [AOR= 0.80*, CI 95% = 0.80 -0.80] and secondary education [AOR = 0.57, CI 95% = 0.56 -0.58] have lower odds of association among older adults with HIV. Regarding TB status, primary education [AOR = 1.08*, CI 95% = 1.06 -1.10] and diabetes [AOR = 1.87*, CI 95% = 1.82-1.91] have lower likelihoods of associations among older adults with TB. Conclusion: There is an urgent need to escalate scientific and political attention to address the HIV/TB burden in older adults and, public health policymakers need to take cognizance of the interdependence of inequality, mobility, and behavioural modification among this high-risk population.